Analisis Kesulitan Siswa Dalam Menyelesaikan Soal Cerita Bangun Ruang Pokok Bahasan Prisma Dan Limas - Triyas Ningrum, Erlina; , Masduki, S.Si, M.Si (2015)
This study aimed to describe the difficulties and the factors in completing the eighth grade students about the subject of the story geometry prism and pyramid. In this study the difficulties students seen from the process of solving the problem follow the steps Polya is to understand the problem, devise a plan of settlement, the settlement of the problem, and check the answers back. This research is a descriptive study with a form of case studies using qualitative approach. The study was conducted at MTs 2 Surakarta . The subjects used in this study were five students in eighth grade. Data collection technique used tests to determine the results of the students' answers, and interviews to determine the difficulties encountered in solving word problems. Results of tests and interviews 5 students known difficulties in solving students' story is about the difficulty in understanding the content, difficulties in determining the formula, the less scrupulous in entering numbers into the formula, and the difficulty of applying the concepts in mathematical calculations.